Analisis Pengaturan Perlindungan Data Pribadi Pengguna Fintech Lending dalam Peraturan OJK Nomor 06/Pojk.07/2022 - Fajrin Putri Carolin; Rani Apriani (Jurnal Ilmiah Wahana Pendidikan, 2022)
The ease of using fintech lending carries a considerable risk, such as services and the leakage of users' personal data. The issuance of OJK Regulation Number 06/POJK.07/2022 aims to strengthen aspects of consumer protection, including fintech lending users as consumers of financial services. Thus, this writing was conducted to find out how the concept of regulating the protection of personal data of fintech lending users in OJK Regulation Number 06/POJK.07/2022 as well as legal sanctions for financial service business actors if they violate the provisions on protection of consumer personal data regulated in the OJK Regulation. The research method used in this study is a normative juridical research approach. Can Key that the substance of the regulation of data and personal information protection in this latest OJK Regulation is stated in detail and clearly. The substance of the regulation of data and information protection as part of the basic behavior of financial services business actors. This OJK regulation also regulates administrative sanctions for parties who do not comply with the provisions, one of which is related to the protection of consumer data and information.